CIDADE E CIDADANIA: UMA PRÁTICA DO ESPAÇO - de Andrade, Marta Mega (PHOÎNIX, 2020)
The aim of this paper is to discuss the relationship of political practices and uses of space. We argue that the consolidation of polis as a political institution produced an abstraction of the social space in order to assert the perspective of exclusive bonds of citizenship as a privilege and territory as patrís. Territory is not the land for inhabitants of all kinds but only citizens, and the civic space as a proposition, as an ideology we may say, guided perceptions of urban space as a space of power signs. As a proposition thus the abstract civic space imposed itself over inhabitants' relations and everyday spatial practices.